Designed to break: planned obsolescence as corporate environmental crime - Bisschop, Lieselot (Crime, law and social change, 2022)
Planned obsolescence is the practice of deliberately designing products to limit their life span to encourage replacement. It is a common business strategy for consumer goods, with far-reaching ecological and social consequences. Here, we examine the definition, causes and consequences of planned obsolescence by using insights from corporate crime literature, integrated with environmental philosophy, management sciences, technology studies and law. Focusing on cases of planned obsolescence in consumer electronics, we show that the concept and procedure carries conceptual ambiguity and moral ambivalence, bearing diffuse harms, benefitting short-term corporate profit but undermining consumer confidence, and posing a major barrier to environmental sustainability. We discuss the system lock-ins driving companies to engage in planned obsolescence, and reframe the practice as a form of corporate environmental crime.